Aplikasi Antrean Interkoneksi Mobile-Desktop Menggunakan Algoritma MLFQ dengan Metode Multi Channel Single Phase - Suryani Suryani; Fatmasari Fatmasari; Nurdiansah Nurdiansah; Sri Wahyuni (JURIKOM (Jurnal Riset Komputer), 2023)
Queue problems are often encountered in everyday life, especially when making transactions at banks. Customers need a lot of time to get a service, so there are many customer complaints related to queues that drain time and energy. Therefore, an increase in service is needed to provide satisfaction and convenience to customers in transactions. By using the Multilevel Feedback Queue algorithm and the Multi-Channel Single Phase method, scheduling by entering processes into several queues, the scheduling algorithm allows a process to move from one queue to another. The Android and desktop mobile interconnect queue application was built as a solution to the problem. The desktop platform for services to customers who come directly (offline) to the Bank is to take a queue number at the bank while tellers and customer service function make calls. Meanwhile, mobile android is for customers who register online, namely by taking a queue number online anytime and anywhere, then customers can see the queue number being served. The research objective is to build a queuing application that can facilitate customers in making transactions, especially getting queue numbers online, minimizing waiting time at queue outlets, and automatically calculating the average service time. The research results are in the form of desktop applications that automatically generate queue numbers of android and with one source of queue arrivals.